Effect of Ascorbic Acid and Potassium Chloride Supplementation on Performance and Some Physiological Parameters in Broiler Chicks Reared under Summer Condition - Tayeb, Ihsan T.; Yokhana , Johnny S.; Amedy, Vahel J.A. (International Journal of Poultry Science, 2011)
A total of 420, one day-old broiler chickens were randomly divided into 4 groups and kept under elevated summer temperature to investigate the effect of ascorbic acid and potassium chloride on the productive performance Live Body Weight (LBW), Body Weight Gain (BWG), Feed Consumption (FC), Feed Conversion Ratio (FCR), Mortality, Dressing Percentage (DP) and blood parameter (hemoglobin (Hb), Packet Cell Value (PCV), Red Blood Cell (RBCs), pH and serum glucose) and rectum temperature. Heat stress was associated with an increase in FCR and mortality and a decreased LBW, BWG and FC of birds. Ascorbic acid and potassium chloride supplementation during heat stress had a beneficial effect on LBW, BWG, FC, FCR, DP, mortality, pH, Serum Glucose and rectum temperature.